HOW TO CHOOSE MEDIUM OF COMMUNICATION - Yadav, Ritu (Innovative Research Thoughts, 2018)
Today, just like forty years ago, we continue to instruct students in the same communication methods. This may and should be considered as an indication of the ongoing significance of these models in emphasising important aspects of that process for students who are breaking down the process for the first time. However, it is still true that the area of communication has advanced significantly since the 1960s, and it is possible that it is necessary to update our models in order to take this advancement into account. the traditional communication models, such as Shannon's information theory model (the active model), a cybernetic model that includes feedback (the interactive model), an intermediary model (“sometimes referred to as a gatekeeper model of the two-step flow), and the transactive model, are taught to students when they are first introduced to interpersonal communication and mass communication. These models include: the active model; a cybernetic model that includes feedback; the interactive model; an intermediary model; and the transactive model. After that, a brand new ecological model of communication is presented, which, it is believed, would more directly map to the variety of topics that are currently being researched and taught in the area of communication today. This model makes an attempt to capture the fundamental interaction of language, medium, and message that enables communication, as well as the aspects of each element that are socially constructed, as well as the relationship of creators and consumers of messages both to these elements and to each other.